Drag reduction by underwater undulatory swimming? An experimental and numerical approach - Hochstein, S.; Pacholak, S.; Brücker, C.; Siebert, T.; Blickhan, R. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
From fish locomotion we learned that low drag values can be achieved during active propulsion. Thereby a carefully adjusted traveling body wave pumps the fluid caudally. Similar to an active flapping plate (Taneda & Tomonari 1974) the usage of a sophisticated body movement reduces and partly prevents the flow separation along the body (e.g., Anderson et al. 2001). The fish use the tail fin to control the generated vortices (Anderson et al. 1998). Despite of the anatomical limitations of the human body (non-smooth and segmented body with limited flexibility) swimmers try to copy successful strategies such as undulatory swimming from fish locomotion. Moreover, it is still unclear whether and, if yes, to what extend the human swimmers are able to reduce drag values during the underwater phases after start and turn. One possibility to investigate this question is to compare passive drag (during gliding) and active drag (during active propulsion). Passive drag can be determined by measuring deceleration or by measuring the force by pulling a subject. Due to the intertwining of drag and propulsion in swimming there is no satisfactory method for a direct experimental determination of active drag. Only for front crawl swimming it is possible to judge active drag by the MAD-system (Measure Active Drag; Hollander et al. 1986). However, this method is not suitable for undulatory swimming. This requires the usage of more complex tools such as Particle Image Velocimetry (PIV) (e.g., Matsuuchi et al. 2009; Hochstein & Blickhan 2011) and Computational Fluid Dynamics (CFD, e.g. von loebbecke et al. 2009; Cohen et al. 2012; Hochstein et al. 2012). The latter provides forces on the moving swimmer during a kick cycle (e.g., von loebbecke et al. 2009). Net forces on the undulating swimmer have been elegantly calculated using smoothed particle hydrodynamics (Cohen et al. 2012). There was no attempt to calculate the drag coefficient during undulatory swimming and the previous CFD studies are not validated. The main goal of this paper is to calculate the drag coefficient during gliding and during active undulatory swimming using numerical flow simulations of a scanned female swimmer and to check whether the swimmer is able to swim with drag coefficients comparable to those for gliding. The presented work only considers the local experimental flow fields with the aim to validate the numerical calculations. The used numerical simulations are the first which were partly validated by the qualitative comparison with the experimental flow field of the same swimmer with identical kinematics. With the local vortices, it is possible to estimate the amount and the loss of the transferred momentum.